MEMBANGUN PENDIDIKAN KARAKTER DENGAN BERKESENIAN - Ria Intani T (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2021)
Abstract: The Character Education Strengthening Program or abbreviated as PPK (Penguatan Pendidikan Karakter) began to be implemented in the formal education environment (schools) in the even semester of the 2017-2018 school year. There are many definitions regarding the term character. One of them, according to the Directorate General of Primary and Secondary Education, Ministry of Education, Culture, Research and Technology, character is defined as a way of thinking and behaving that characterizes each individual to live and work together, both within the family, community, nation and state. In fact, there are many ways to build character education. Not only in the formal education environment through school subjects, but also outside formal education through the arts. The purpose of this research is to disseminate insight into the breadth of ways in building character education. This research is descriptive with the methods used are observation, active participation, and interviews. The results of the study show that